2019
DOI: 10.1136/thoraxjnl-2018-212102
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double-blind, placebo-controlled pilot trial of omeprazole in idiopathic pulmonary fibrosis

Abstract: BackgroundCough is a common, disabling symptom of idiopathic pulmonary fibrosis (IPF), which may be exacerbated by acid reflux. Inhibiting gastric acid secretion could potentially reduce cough. This study aimed to determine the feasibility of a larger, multicentre trial of omeprazole for cough in IPF, to assess safety and to quantify cough.MethodsSingle-centre, double-blind, randomised, placebo-controlled pilot trial of the proton pump inhibitor (PPI) omeprazole (20 mg twice daily for 3 months) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
0
56
0
3
Order By: Relevance
“…As a result, the majority of Phase II and III clinical trials in IPF have used the measure of lung function as the primary endpoint. Recently, there has been considerable work on quality of life and symptoms (including cough and reflux) [59]. Furthermore, several groups have pooled clinical trial databases to examine treatment effects of drugs on clinical endpoints including mortality and respiratory hospitalizations [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the majority of Phase II and III clinical trials in IPF have used the measure of lung function as the primary endpoint. Recently, there has been considerable work on quality of life and symptoms (including cough and reflux) [59]. Furthermore, several groups have pooled clinical trial databases to examine treatment effects of drugs on clinical endpoints including mortality and respiratory hospitalizations [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a cough trial with proton pump inhibitors showed that proton pump inhibitors increase the nonacidic components of reflux [137]. A recently published pilot trial on omeprazole in IPF demonstrated that omeprazole is well tolerated; a small excess of lower respiratory tract infection was evidenced together with a minor reduction in FVC associated with use of omeprazole [138]. In order to give a definitive answer on the effects of GOR therapy in patients with IPF, further prospective, randomised studies are needed to shed light on this specific aspect.…”
Section: Gor Diseasementioning
confidence: 99%
“…No changes were observed in FVC, T L,CO or quality of life assessments during three months of follow-up. The study results can support the efficacy of omeprazole in managing cough in IPF patients and indicate a need of additional, multicentre trials with larger patient populations [280].…”
Section: Commentarymentioning
confidence: 56%